The Study of the Effect of Capacity Increase and Photovoltaic Placement on Power Loss, Voltage Profile by Considering THDv - Syukri Yunus; R.H. Sukma (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2021)
The application of Photovoltaic (PV) is one solution to the increasing demand for electrical energy. However, the application of photovoltaic (PV) must be in the right location and capacity so that the power loss you want to reduce is large and the voltage profile is good. Photovoltaic (PV) generates DC voltage which is then required by an inverter to convert it to AC. The inverter is a non-linear load that produces harmonics. Harmonics in an electric power system can be known from Total Harmonic Distortion (THD). The purpose of this study is to determine the optimal location of placement (PV) and its maximum capacity so that the power loss is smaller. The resulting voltage and THD profile conform to the permitted standards. The methods used in determining the optimal location of photovoltaic (PV) are Loss Sensitivity Factor (LSF) and Voltage Sensitivity Index (VSI). ETAP 16 software is used for power and harmonic flow simulation. From this research, the most optimal photovoltaic (PV) placement is on bus 10 (bus 283 T) with a maximum capacity of 3255 kVA. This placement location provides minimal power loss and a good voltage profile taking into account the permitted standard THDv.